Infinite Dimensional Maximal Torus Revisited - Mohamed Lemine H. Bouleryah; Akram Ali; Piscoran Laurian-Ioan (Mathematics)
Let <semantics>Tm</semantics> be the maximal torus of a set of <semantics>m×m</semantics> unitary diagonal matrices. Let <semantics>T</semantics> be a collection of all maps that rigidly rotate every circle of latitude of the sphere with a fixed angle. <semantics>T</semantics> is also a maximal torus, and we shall prove in this paper that <semantics>T</semantics> is the topological limit inf of <semantics>Tm</semantics>.